Carbon nanotube enhanced carbon Fibre-Poly(ether ether ketone) interfaces in model hierarchical composites. (12th April 2022) - Lamorinière, Steven; Jones, Mitchell P.; Ho, Kingsley; Kalinka, Gerhard; Shaffer, Milo S.P.; Bismarck, Alexander
Abstract: Poly (ether ether ketone) (PEEK) has a high continuous service temperature, excellent mechanical properties, and good solvent and abrasion resistance, which can be further improved through the addition of carbon nanotubes (CNTs). CNT-PEEK nanocomposites are promising matrices for continuous carbon fibre composites; powder processing can mitigate the high melt viscosities in these systems. In this study, model single fibre (hierarchical) composites were produced by embedding sized and desized carbon fibres in nanocomposite CNT-PEEK powders followed by single fibre pull-out tests to assess interfacial characteristics. Carbon fibre-PEEK interfacial shear strength is typically 40–45 MPa. Increasing CNT loadings increased fibre-matrix interfacial shear strength linearly up to ∼70 MPa at 5.0 wt%, which was attributed to the CNT-based mechanical modification of the PEEK matrix. Apparent interfacial shear strength was inversely correlated with the embedded fibre length irrespective of carbon fibre sizing or CNT loading, indicating brittle fracture of the fibre-matrix interface. Pulled out carbon fibres were still coated with the matrix, which indicated strong adhesion at the interface in all samples, likely related to a transcrystalline region. Adhesion was, however, negatively affected by the presence of epoxy sizings. Frictional shear strength was independent of embedded fibre length and CNT content for all samples. Graphical abstract: Image 1